2006
DOI: 10.2139/ssrn.895246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disasters on International Trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…Gassebner et al (2006) quantitatively estimated these impacts on international trade at global scale. They found that disasters reduced trade in both exporter and importer countries.…”
Section: Y Meng Et Al: the Asymmetric Impact Of Natural Disastersmentioning
confidence: 99%
See 2 more Smart Citations
“…Gassebner et al (2006) quantitatively estimated these impacts on international trade at global scale. They found that disasters reduced trade in both exporter and importer countries.…”
Section: Y Meng Et Al: the Asymmetric Impact Of Natural Disastersmentioning
confidence: 99%
“…From a global perspective, natural disasters have negative trade effects (Oh and Reuveny, 2010;Gassebner et al, 2006). However, if we focus on a specific country or region, the result may be totally different.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Natural disasters may affect international trade tax revenues through their impacts on the flows of international trade. Gassebner, Keck and The (2006) argue that the impact of a disaster on international trade can be transmitted either directly or indirectly. Direct impacts on exports can occur due to human losses and injuries (to company staff and manpower) and the destruction and damage of physical capital and equipment in the export sector.…”
Section: Trade Transaction Taxmentioning
confidence: 99%
“…Studies including Anbarci, Escaleras and Register (2005), Kahn (2005), Gassebner, Keck and The (2006) highlight that governance is a key driver in determining the magnitude of the effect caused by natural disasters. Countries that are well-governed are better at coping with disasters.…”
Section: The Role Of Quality Of Governancementioning
confidence: 99%